PERAN GURU DALAM MEMBINA KARAKTER PEDULI LINGKUNGAN SISWA PADA PROGRAM PASUKAN SEMUT (SEJENAK MEMUNGUT) SAMPAH DI SEKOLAH ALAM PACITAN - Fivian Prameswari Azizah; Afid Burhanuddin; Lina Erviana (Jurnal Pendidikan Dasar Borneo (Judikdas Borneo), 2025)
This study aims to describe the implementation of the SEMUT (Sejenak Memungut) Garbage Troop program at Alam Pacitan School and to describe the role of teachers in fostering students environmental awareness through the program. This study uses a qualitative descriptive approach with data sources from grade I–III teachers and representatives of grade III students at Alam Pacitan School. Data collection techniques used interviews, observation, and documentation, as well as credibility testing through source and technique triangulation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results of the study indicate that the SEMUT Troop program has been implemented according to aspects and indicators, including planning, implementation, and evaluation. However, the level of community participation still needs to be improved. The role of teachers in fostering environmental awareness is evident in various concrete actions carried out with full commitment. Teachers as educators who set an example by getting used to disposing of waste and managing waste properly. Teachers provide appreciation for efforts made as motivators. Teachers as mentors demonstrate commitment in creating activities that reduce the use of single-use items. Teachers train students by inviting them to do direct practice. Teachers as facilitators who provide a place for skill development through innovative project activities that are in line with the 5R principles (Reduce, Reuse, Recycle, Replant, Replace).